Crosstalk Between Abnormal TSHR Signaling Activation and PTEN/PI3K in the Dedifferentiation of Thyroid Cancer Cells - Feng, Fang; Han, Huiqin; Wu, Shuqi; Wang, Hui (Frontiers in Oncology, 2021)
Iodide uptake and the metabolism of thyroid cells are regulated by thyrotropin (TSH)-TSH receptor (TSHR) signaling. Thus, it is necessary to elevate serum TSH levels by T4 withdraw or rTSH administration to facilitate radioiodide (131I) therapy for differentiated thyroid cancer (DTC). However, non-iodide-avid metastases of DTC which is dedifferentiated do not respond to stimulation by high levels of TSH, suggesting abnormal TSH-TSHR signal transduction in cancer cells. In addition, PI3K/AKT/mTOR signaling activation has been shown to be associated with the dedifferentiated phenotype of thyroid cancer, but the mechanism remains elusive. Therefore, in this study, we aimed to explore the role of abnormal TSH-TSHR signaling activation in regulating iodide uptake and cell mobility in thyroid cancer and its relationship with PI3K/AKT/mTOR signaling. We found that in thyroid cancer cells, TSH binds TSHR coupled to the Gα12/13 protein and then activates RhoA through interacting with leukemia associated RhoA guanine exchange factor (LARG). This results in a promigration tumorigenic phenotype independent of canonical TSHR-GαS signaling that regulates the expression of molecules involved in iodine uptake and metabolism. We observed that signaling pathways downstream of Gα12/13 signaling were increased, while that of Gαs signaling was decreased in thyroid cancer cells undergoing dedifferentiation compared to control cells following stimulation with different levels of TSH. PI3K/AKT/mTOR signaling activation enhanced Gα12/13 signaling through increasing LARG levels but also inhibited the expression of molecules downstream of Gαs signaling, including thyroid-specific molecules, and iodide uptake. In summary, our results demonstrate the noncanonical activation of TSH-TSHR signaling and its role in increasing the cell mobility and dedifferentiation of thyroid cancer through crosstalk with PI3K/AKT/mTOR signaling.